MATHEMATICAL MODEL FOR INTERACTION OF THERAPIST AND CLIENT WITH BIPOLAR DISORDER - Ainiyah, Fariyatul
Bipolar disorder is a mental disorder that is experienced by many people in Indonesia and in the world. This disorder causes extreme changes in mood so it reaches the stage of interfering with the ability to do daily work. Bipolar disorder is also called manic-depressive disorder because of the fluctuating mood changes between manic episodes (happiness) and depression (sadness). To achieve stability, people with bipolar disorder need to take a series of appropriate treatments. One treatment that has a big influence is therapy. The relationship between therapist and client becomes one of the factors that influence the success of therapy. In this final project, two mathematical models related to mood swing from bipolar disorder are shown. Both of these models have different approaches. The first model focuses on mood swings and uses the van der Pol nonlinear oscillation equation. While the second model uses the behavioral approach system (BAS) theory approach and looks at the interaction between mood and expectations. From these two models, a bipolar client and therapist interaction model is constructed. The construction of this interaction model aims to see the mood dynamics of the therapist and client during the therapy process. Then with a slight modification to the therapist-client interaction model, a model for the caregiver-client interaction is constructed.